Advantages and Disadvantages of L1 in BA English Language Classes - Guerrero Derramona, Maria Guadalupe (CIEX JOURNAL, 2023)
The advantages and disadvantages present to students and teachers different perspectives to take into account the use of L1 in English language with the purpose to develop the four skills. This research presents a study about the use of L1 in BA English classes at CIEX, with the intention to find different ways to teach English considering the L1 use in English classes. The methodology included qualitative approach and phenomenology to understand the advantages and disadvantages about the L1 use in English classes at CIEX BA, considering the different factors that are involved with students and teacher. The main findings of the study demonstrated that the use of L1 is important in the classroom to help student’s understanding and that depending on the students’ level could be the use of L1.